Utilization of Plants in Agroforestry at Sungai Buluh LPHN, West Sumatra - Putri, Novia Anas; Chairul, Chairul; Solfiyeni, Solfiyeni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Agroforestry is an intensive land management system combining forestry, agricultural, fruit, and medicinal plants to achieve optimal results while ensuring land conservation and local community practices. This research aims to explore the utilization of agroforestry in the LPHN (Nagari Forest Management Institute) Sungai Buluh, Padang Pariaman Regency. The study was conducted from December to February 2024 using the transect method. The results revealed that the community utilizes 25 types of medicinal plants to treat various ailments such as fever, diarrhea, coughs, colds, wounds, digestive issues, and joint pain. The most commonly used plant part is the leaf, due to its practicality and easy accessibility. These medicinal plant uses reflect the community's traditional knowledge passed down through generations. Furthermore, non-timber forest products were categorized into two groups based on their usage: 4 types of food ingredients and 4 types of natural dyes or cooking ingredients. In conclusion, the study highlights the significant role of local agroforestry practices in maintaining health and biodiversity. The implications of this research suggest the need for sustainable agroforestry management to preserve both ecological and cultural values.